The Market Reaction to Stock Split Announcement - Bella Firda Indriani (Profesional Muda Cendekia Publishing, 2022)
This study aims to examine the market reaction to the stock split announcement. The market reaction in this research will be proxied with abnormalities that occur around the day of the stock split announcement. This study also examines the relationship between firm size and abnormal returns around the day of the stock split announcement. The population in this study are companies listed on Indonesia Stock Exchange that announced a stock split from 2012-2019. By using purposive sampling, the total sample used in this study was 72 companies. This study's results indicate an abnormal return around the day of the stock split announcement. This study also shows a negative but insignificant relationship between firm size and abnormal returns around the day of the stock split announcement.